Pulses: Poor man's food or future super food? - Jayasena, Vijay; Abbas, S. (Australian Institute of Food Science and Technology Inc., 2016)
The humble pulse was once the favoured food of many ancient civilisations. Could it also be the answer to sustainable food in the 21st century?